PERBANDINGAN PENGARUH PEMBERIAN ANALGETIK COX-2 DENGAN ASAM MEFENAMAT TERHADAP RASA NYERI PASCA ODONTEKTOMI (IMPAKSI KELAS 1, MOLAR 3 RAHANG BAWAH) - Dicky Kresnadi Rahmanto; Kuswartono Mulyo (Jurnal Kedokteran Diponegoro, 2016)
Background: Sore is a common gripe and frightening experience for patients post odontectomyso patients requiredof proper and good treatment. Mefenamic acid analgesic drug effects can not always be achieved the maximum in comparison with the type of drug effects etoricoxib that can achieve maximum results with appropriate and well.